Pharmaceutical payments to certified oncology specialists in Japan in 2016: a retrospective observational cross-sectional analysis - Akihiko Ozaki; Toyoaki Sawano; Tetsuya Tanimoto; Hiroaki Saito; Yosuke Onoue; Yuki Shimada; Yurie Somekawa; Aritsune Tsuji (BMJ Open)
Objective This study investigated payments made by pharmaceutical companies to oncology specialists in Japan, what the payments were for and whether the receipt of such payments contravened any conflict of interest (COI) regulations.Design, setting and participants Payment data to physicians, as reported by all pharmaceutical companies belonging to the Japan Pharmaceutical Manufacturers Association, were retrospectively extracted for 2016. Of the named individual recipients of payments, all certified oncologists were identified, using certification data from the Japanese Society of Medical Oncology (JSMO). The individual specialisations of each of the oncologists was also identified.Outcome Payments to individual cancer specialists and what they were for were identified. Factors associated with receipt of higher value payments and payment flows to specialties were determined. Companies selling oncology drugs with annual sales of ≥5 billion yen (£33.9 million, €40.2 million and $46.0 million) (high revenue-generating drugs) were identified.Results In total, 59 companies made at least one payment to oncologists. Of the 1080 oncology specialists identified, 763 (70.6%) received at least one payment, while 317 received no payment. Of the 763, some 142 (13.1%) receiving at least 1 million yen (£6,800, €8,000 and $9200) accounted for 71.5% of the total. After adjustment of covariates, working for university hospitals and cancer hospitals and male gender were key factors associated with larger monetary payments. Payments preferentially targeted on cancer specialties using high revenue-generating drugs. The JSMO has its own COI policy for its members, but the policy did not mention any specific guidelines for certified oncology specialists.Conclusion Financial relationships were identified and quantified between pharmaceutical companies and oncology specialists, but the extent and worth varied significantly. Given the frequency and amounts of money involved in such linkages, it would be beneficial for specific COI regulations to be developed and policed for oncologists.